2003
DOI: 10.1300/j092v11n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Activity Limitations/Participation Restrictions Among Fibromyalgia and Chronic Fatigue Syndrome Patients

Abstract: Fibromyalgia (FM) and Chronic Fatigue Syndrome (CFS) are related yet overlapping disorders; the current case definitions prohibit a clear-cut differential diagnosis. These diagnostic criteria mainly address the impairment level of the World Health Organization's International Classification of Functioning, Disability and Health. This study aimed at comparing activity limitations and participation restrictions in patients with FM (n = 90) and CFS (n = 47). The Chronic Fatigue Syndrome Activities and Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…the presence of tender points assessed using a pressure algometer) was similar to those of the patients with FMS (Goldenberg et al, 1990). Using a validated measure (Nijs et al, 2003a, b), it was concluded that FMS and CFS patients present with nearly identical activity limitations and participation restrictions (Nijs et al, 2003b). Joint hypermobility is defined as an increased mobility of small and large joints beyond the range of motion considered normal (Hudson et al, 1995;Karaaslan et al, 2000).…”
Section: Introductionmentioning
confidence: 90%
“…the presence of tender points assessed using a pressure algometer) was similar to those of the patients with FMS (Goldenberg et al, 1990). Using a validated measure (Nijs et al, 2003a, b), it was concluded that FMS and CFS patients present with nearly identical activity limitations and participation restrictions (Nijs et al, 2003b). Joint hypermobility is defined as an increased mobility of small and large joints beyond the range of motion considered normal (Hudson et al, 1995;Karaaslan et al, 2000).…”
Section: Introductionmentioning
confidence: 90%